1996
DOI: 10.1097/00007691-199608000-00033
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Electrophoresis for Drug Analysis in Body Fluids

Abstract: Capillary zone electrophoresis (CZE) and micellar electrokinetic capillary chromatography (MECC) represent attractive methods for the determination of drugs and metabolites in body fluids. In CZE, minute (nanoliter) quantities of samples are applied to the beginning of a fused-silica capillary filled with buffer. On application of a high-voltage DC field, charged solutes begin to separate and are swept through the capillary by the combined action of electrophoresis and electroosmotic bulk flow and are on-colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Most methods, however, are unable to efficiently determine all three compounds simultaneously. Recently, capillary electrophoresis (CE) [11] proved to be a powerful alternative to chromatographic techniques in the analysis of drugs and some of their metabolites in body fluids [12,13]. The main advantages of CE are high separation efficiency, short analysis time, and low operational cost.…”
Section: Introductionmentioning
confidence: 99%
“…Most methods, however, are unable to efficiently determine all three compounds simultaneously. Recently, capillary electrophoresis (CE) [11] proved to be a powerful alternative to chromatographic techniques in the analysis of drugs and some of their metabolites in body fluids [12,13]. The main advantages of CE are high separation efficiency, short analysis time, and low operational cost.…”
Section: Introductionmentioning
confidence: 99%
“…In the above-mentioned earlier works, high mmolar levels have been determined with reproducibilities in the range of about 2±5% for repeatability (n & 10) and of about 4± 12% for interday precision, respectively ( [2,26], reviews in [11,30,31]; compare Table 13). Generally, CE suffers from a relatively low concentration sensitivity.…”
Section: Introductionmentioning
confidence: 85%
“…It was found out that the kinetics of the interactions is strongly correlated to the hydrolysis rate of cisplatin. As the major adducts, [Pt(NH 3 ) 2 (N7-GMP) 2 ] 22 and [Pt(NH 3 ) 2 (N7-AMP) 2 ] 22 were identified, though resulted from interactions with thymidine 5'-monophosphate (TMP) and cytidine 5'-monophosphate (CMP) were only trace adduct peaks that remained for this reason unidentified. The results of competitive studies shown in Fig.…”
Section: Platinum Complexesmentioning
confidence: 99%
“…In order to add an extra selectivity dimension to CE data, the effect of Met on the binding of oxaliplatin to GMP was explored by means of a hyphenated CE-ESI-MS system [46]. Without Met the main reaction product was the bis-GMP adduct (as described in Section 5.1), whereas Met forced [Pt(Dach)(GMP) 2 ] 22 to enter a ligand-exchange reaction producing, along with the major adduct, [Pt(Dach)(Met-S,N)]…”
Section: Amino Acidsmentioning
confidence: 99%